1990
DOI: 10.1093/jn/120.4.404
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Protein-Energy Malnutrition and Refeeding on the Adherence of Salmonella typhimurium to Small Intestinal Mucosa and Isolated Enterocytes in Rats

Abstract: The adherence of fimbriated (Fim+) and nonfimbriated (Fim-) strains of Salmonella typhimurium to both isolated intestinal epithelial cells and intact intestinal mucosa of healthy and malnourished rats was investigated. Fim+ strains bound in significantly higher numbers than did Fim- strains to enterocytes isolated either from healthy or malnourished rats. Adherence to intact intestinal mucosa in situ was demonstrable with both Fim+ and Fim- bacteria, but Fim+ strains were preferred because they showed approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Giardiasis affects young children, homosexual, hypergammaglobulinaemic, immunocompromised and malnourished individuals and has the highest prevalence of 20% in developing world (Gardner and Hill 2001;Eckmann 2003). Adequate and prompt correction of the nutritional status is important to reduce morbidity and mortality associated with the immune suppression caused by malnutrition (Scrimshaw and Sangiovanni 1997;Omoike et al 1990). It has been reported that renourishing with proper diet restores the morphology and physiology of the intestine leading to normalisation of intestinal permeability and gut atrophy (Castillo et al 1991;Poullain et al 1991;Boza et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Giardiasis affects young children, homosexual, hypergammaglobulinaemic, immunocompromised and malnourished individuals and has the highest prevalence of 20% in developing world (Gardner and Hill 2001;Eckmann 2003). Adequate and prompt correction of the nutritional status is important to reduce morbidity and mortality associated with the immune suppression caused by malnutrition (Scrimshaw and Sangiovanni 1997;Omoike et al 1990). It has been reported that renourishing with proper diet restores the morphology and physiology of the intestine leading to normalisation of intestinal permeability and gut atrophy (Castillo et al 1991;Poullain et al 1991;Boza et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…(1,7,9,11,15,24,36), only the role of type 1 fimbriae of Salmonella typhimurium in pathogenesis has been extensively explored. Although type 1 fimbriated bacteria have been shown to bind eukaryotic cell lines, freshly isolated enterocytes, and intestinal epithelial tissue, the role of these fimbriae in pathogenesis remains controversial (13,22,27). The role of other fimbriae in salmonellosis is unexplored except for recent evidence which implicates type 3 fimbriae of S. typhimurium and Salmonella entertidis in binding of these strains to type V collagen (34).…”
mentioning
confidence: 99%